Pengaruh Loan To Deposit Ratio (Ldr), Non-Performing Loan (Npl) Dan Beban Operasional Pendapatan Operasional (Bopo) Terhadap Return On Equity (Roe) (Studi Pada Pt Bank Mandiri (Persero) Tbk Periode 2013-2024) - Ahmad Oky Subakti; Achmad Ludvy (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. The purpose of this study is to determine the effect of Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL) and Operating Expenses to Operating Income (BOPO) on Return on Equity (ROE) at PT Bank Mandiri (Persero) Tbk. Both partially and simultaneously. The research method used is the associative cause method with a quantitative approach. The sample used is the financial statements of PT Bank Mandiri Tbk for 12 (twelve) years. Data analysis in this study uses classical assumption tests, multiple regression analysis, hypothesis testing, and coefficient of determination analysis. The results of this study are multiple linear regression equations of Y = 69.6518-0.1458573X1 + 7.327523X2 - 0.6437838 + e. Partially, Loan to Deposit Ratio (LDR) has a significant influence on Return On Equity (ROE) with a significant level of 0.017 < 0.05 with a calculated t value> t table or -2.99> 2.30600. While the Non-Performing Loan (NPL) variable has a significant influence on Return On Equity (ROE) with a significant level of 0.008 < 0.05 with a calculated t value> t table or 3.47> 2.30600. Operating Expenses Operating Income (BOPO) has a significant influence on Return On Equity (ROE) with a significant level of 0.000 < 0.05 with a calculated t value> t table or -11.18> 2.30600. Simultaneously, the Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL), and Operating Expenses to Operating Income (BOPO) significantly influence Return on Equity (ROE) at a significance level of 0.0000 < 0.05, with a calculated F value > F table, or 43.31 > 4.07. The coefficient of determination (Adj R-squared) of 92.03% of the variables Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL), and Operating Expenses to Operating Income (BOPO) influence Return on Equity (ROE). Meanwhile, the remaining 7.97% is influenced by other variables outside the study.